Anomalous arising of left coronary artery from the pulmonary artery (ALCAPA) - Kolesár, Adrián; Toporcer, Tomáš; Vachalcová, Marianna Barbierik; Rohn, Vilém; Molnár, Tomáš; Mad'arová, Tatiana; Lukačin, Štefan (Journal of clinical ultrasound, 2023)
Computed tomography 3D reconstruction of a patient with Bland-White-Garland syndrome showing a dilated right coronary artery and thin left coronary artery.
Keywords: ALCAPA; Pulmonary Artery; anomálie koronárních cév; Bland White Garland Syndrome; syndrom Bland-White-Garland; Coronary Vessel Anomalies; Humans; arteria pulmonalis; počítačová rentgenová tomografie; mitral valve insufficiency; Tomography, X-Ray Computed; lidé; coronary artery anomalies